Treatment of vascular dementia in female rats with AV-001, an Angiopoietin-1 mimetic peptide, improves cognitive function - Gao, Huanjia; Liu, Xianshuang; Venkat, Poornima; Findeis, Elizabeth; Zacharek, Alex; Powell, Brianna; Mccann, Mikkala; Kim, Harold; Zhang, Zhenggang; Chopp, Michael (Frontiers in Neuroscience, 2024)
Background Vascular dementia (VaD) is a complex neurodegenerative disorder. We previously found that treatment of VaD in middle-aged male rats subjected to multiple microinfarction (MMI) with AV-001, a Tie2 receptor agonist, significantly improves cognitive function. Age and sex affect the development and response of VaD to therapeutic intervention. Thus, the present study investigated the therapeutic effect of AV-001 on VaD in aged female rats subjected to MMI. Methods Female 18-month-old Wistar rats were subjected to MMI by injecting either 1,000 (low dose, LD-MMI) or 6,000 (high dose, HD-MMI) cholesterol crystals of size 70–100 μm into the right internal carotid artery. AV-001 (1 μg/Kg, i.p.) was administered once daily after MMI for 1 month, with treatment initiated 1 day after MMI. A battery of behavioral tests to examine sensorimotor and cognitive functions was performed at 21–28 days after MMI. All rats were sacrificed at 1 month after MMI. Results Aged female rats subjected to LD-MMI exhibit severe neurological deficits, memory impairment, and significant white matter (WM) and oligodendrogenesis injury in the corpus callosum compared with control rats. HD-MMI in aged female rats induces significant anxiety- and depression-like behaviors, which were not detected in LD-MMI aged female rats. Also, HD-MMI induces significantly increased WM injury compared to LD-MMI. AV-001 treatment of LD-MMI and HD-MMI increases oligodendrogenesis, myelin and axon density in the corpus callosum and striatal WM bundles, promotes WM integrity and attenuates neurological and cognitive deficits. Additionally, both LD-MMI and HD-MMI rats exhibit a significant increase, while AV-001 significantly decreases the levels of inflammatory factors in the cerebrospinal fluid (CSF). Conclusion MMI reduces oligodendrogenesis, and induces demyelination, axonal injury and WM injury, and causes memory impairment, while HD-MMI induces increased WM injury and further depression-like behaviors compared to LD-MMI rats. AV-001 has a therapeutic effect on aged female rats with MMI by reducing WM damage and improving neuro-cognitive outcomes.